STRATEGI ADAPTASI KARYAWAN PEMUTUSAN HUBUNGAN KERJA (PHK) PT. RAMAYANA LESTARI SENTOSA KECAMATAN MANDAU KABUPATEN BENGKALIS - Ellen Enzelina Simatupang; Ashaluddin Jalil (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
The case of termination of employment that occurred at PT. Ramayana Lestari Sentosa to 70 employees due to the impact of Covid-19, which made the company's turnover decrease. A total of 70 employees who were laid off, there were employees who were married and not employed, 25 of which were 15 people who were rehired, the difference being 10 employees who were married were not rehired. This study uses descriptive qualitative research with snowball by finding informants connecting each other from one informant to another. This study aims to determine how the adaptation strategy of ex-employees after being laid off and to find out the socio-economic conditions of ex-employees after not working. The results of this study were obtained from observations and interviews conducted and found adaptation strategies carried out on former employees who were laid off, namely the Active Strategy of opening a selling, salon and sewing business, the Passive Strategy of making savings and the Network Strategy of asking friends or relatives for help in running the business. In addition, this research also finds social conditions that are well-established towards others and economic conditions are helped. All of the adaptation strategies that are mutually binding are carried out to survive to meet daily needs. Keywords: Termination of Employment, Adaptation Strategies, Socio Economic Conditions